Finger Flexion Contracture: First Manifestation of Gout - Kumar, Ravi (J Orthop Case Rep, 2015)
INTRODUCTION: Tophi can present as a first sign of hyperuricemia but literature has limited reports as far as flexor tendon contracture presenting as a first clinical sign of gout is concerned. We report a case of tophaceous gout with finger flexion contracture as its first sign. CASE REPORT: A 45 years old man presented in our out patient department with complaint of inability to extend middle finger of his left hand along with a mass growing over volar aspect of forearm for over few months. On physical examination a firm – hard mass around 2*2 cm was found over volar aspect of forearm just proximal to flexor retinaculam. MRI showed mass within tendon of FDS. Clinical suspicion of TB tenosynovitis, was kept as a first diagnosis followed by soft tissue neoplasm and subsequently surgical exploration was performed. A whitish chalky infiltration of tendon of FDS, synovial adhesion of other tendons along with median nerve embedded within hypertrophied synovium of flexor tendon noted. Patient underwent synovectomy and excision of tendon of FDS to middle finger Following histo-pathological evaluation a diagnosis of tophaceous gout was made with serum uric acid level being 8.6 mg/dl. CONCLUSION: A review of the literature reveals that gouty arthritis of the wrist is rare in isolation. Gout at the wrist as the initial appearance of the condition occurs between 0.8 to 2% of all gout cases. Gout occurs when serum uric acid levels are persistently higher than 6.8mg/dl. Since tophaceous gout can be seen scarcely in well controlled hyper-uricaemic patient thus making preoperative diagnosis of intratendinous tophi even more strenuous.